The Cohesin Subunit Rad21 Is Required for Synaptonemal Complex Maintenance, but Not Sister Chromatid Cohesion, during Drosophila Female Meiosis - Urban, Evelin (Public Library of Science, 2014)
Replicated sister chromatids are held in close association from the time of their synthesis until their separation during the next mitosis. This association is mediated by the ring-shaped cohesin complex that appears to embrace the sister chromatids. Upon proteolytic cleavage of the α-kleisin cohesin subunit at the metaphase-to-anaphase transition by separase, sister chromatids are separated and segregated onto the daughter nuclei. The more complex segregation of chromosomes during meiosis is thought to depend on the replacement of the mitotic α-kleisin cohesin subunit Rad21/Scc1/Mcd1 by the meiotic paralog Rec8. In Drosophila, however, no clear Rec8 homolog has been identified so far. Therefore, we have analyzed the role of the mitotic Drosophila α-kleisin Rad21 during female meiosis. Inactivation of an engineered Rad21 variant by premature, ectopic cleavage during oogenesis results not only in loss of cohesin from meiotic chromatin, but also in precocious disassembly of the synaptonemal complex (SC). We demonstrate that the lateral SC component C(2)M can interact directly with Rad21, potentially explaining why Rad21 is required for SC maintenance. Intriguingly, the experimentally induced premature Rad21 elimination, as well as the expression of a Rad21 variant with destroyed separase consensus cleavage sites, do not interfere with chromosome segregation during meiosis, while successful mitotic divisions are completely prevented. Thus, chromatid cohesion during female meiosis does not depend on Rad21-containing cohesin.